The effects of different doses of alfentanil and remifentanil on the intubating conditions without the use of muscle relaxants [Deǧişik dozlarda alfentanil ve remifentanilin kas gevşeticisiz endotrakeal entübasyon koşullarina etkileri] - (:unkn) unknown (My University, 2005)
Aim: In this study, we compared the effects of alfentanil (10 μg kg -1, 15 μg kg-1) and remifentanil (1 μg kg -1, 1,5 μg kg-1) on intubating conditions after propofol induction while breathing 2 MAC sevoflurane and % 70 N2O. Materials and Methods: Seventy fifth patients, aged 20-60 years, scheduled for elective surgery were randomly assigned to 5 groups (n=15). Anesthesia was induced with 1.5-2 mg kg-1 propofol. Patients were ventilated with 2 MAC sevoflurane, % 70 N2O in oxygen via face mask. Groups C, A10, A15, R1, R1.5 received 1,5 mg kg-1 succinylcholine, 10 μg kg -1 alfentanil, 15 μg kg-1 alfentanil, 1 μg kg -1 remifentanil and 1.5 μg kg-1 remifentanil respectively. Endotracheal intubation was performed at 90th seconds following. Ease of ventilation, jaw relaxation, position of vocal cords, Cormaek-Lehane classification, and patients' response to intubation and inflation of endotracheal tube cuff were assessed. Results: In group A10, Cormack-Lehane classification was significantly higher and vocal cords were mobile compared to other groups (p<0.05). Patients' cough response to intubation and inflation of endotracheal tube cuff were significantly higher in group A10 compared to groups C, R1 and R1.5 and in group A15 compared to groups C and R1.5 (p <0.01). In all opioid groups, mean arterial pressures after intubation were significantly lower compared to control (p<0.05). In groups R1 and R1.5 heart rates were significantly lower compared to control (p<0.01). Conclusions: After propofol induction, remifentanil with 2 MAC sevoflurane and % 70 nitrous oxide decreases cough as well as hemodynamic responses to intubation done without neuromuscular blockade.
Keywords: Alfentanil; Intubation; Propofol; Remifentanil